Inhospital Exercise Training in Children With Cancer: Does It Work for All? - Morales, Javier S.; Padilla, Julio R.; Valenzuela, Pedro L.; Santana-Sosa, Elena; Rincón-Castanedo, Cecilia; Santos-Lozano, Alejandro; Herrera-Olivares, Alba M.; Madero, Luis; San Juan, Alejandro F.; Fiuza-Luces, Carmen; Lucia, Alejandro (Frontiers in Pediatrics, 2018)
Purpose: Physical exercise training has been proposed as an effective strategy to counteract the weakening effects of pediatric cancer treatment. We aimed to analyze the prevalence of ‘responders’ and ‘non-responders’ to inhospital exercise training in children with cancer and to identify the factors that could influence responsiveness. Methods: We performed an ancillary analysis of the randomized controlled trial “Physical activity in Pediatric Cancer” (NCT01645436), in which 49 children with solid tumors were allocated to an inhospital exercise intervention or control group. The present study focused on the children in the former group (n=24, 10±1 years), who performed three weekly training sessions (aerobic + strength exercises). The duration of the intervention was 19±2 weeks (i.e., from the start to the end of neoadjuvant chemotherapy treatment). A responder-vs-non-responder analysis was performed for physical capacity-related endpoints (five-repetition maximum strength and functional mobility tests, and cardiorespiratory fitness (CRF)). Results: Most participants improved their performance in the strength tests (rate of responsiveness >80%, p<0.001). By contrast, no significant improvements were observed for the functional ability tests or CRF (p>0.05, rate of responsiveness ~50%). No differences between responders and non-responders were observed for sex, age, type of cancer or treatment (i.e., including or not anthracyclines or radiotherapy). However, significant differences (p<0.05) were observed between responders and non-responders for baseline performance in the time up and go test and CRF, and a significant (p<0.05) inverse relationship was found between baseline performance and relative improvement for most endpoints. Conclusions: Although most children improved their muscle strength after an inhospital exercise intervention, a considerable individual variability was observed in the training response of functional mobility and CRF. Baseline performance appeared as the major conditioning factor of responsiveness for the study endpoints, with those fittest children at the start of treatment showing the lowest responses. Efforts to individualize exercise prescription are needed to maximize responsiveness in pediatric cancer patients.